'about gays by gays': the politics of representation in early Australian gay film culture, 1971–1982. Issue 1 (2nd January 2019) - Matheson, Jessie
ABSTRACT: Following major film censorship reform in 1971 gay and lesbian Australians were, for the first time, able to see and tell their stories on screen. This change coincided with internationally revolutionary moments of gay and lesbian activism, which were largely centred around the notion of visibility. The new representational opportunities that gay and lesbian film offered quickly became tied to the political imperatives of the Australian iteration of this activist movement. A film sensibility also soon developed that was both particularly queer and particularly Australian. This article explores the extent to which the question of film audience became politicised in Australia following censorship reform in 1971, until the early 1980s, and the implications this had for gay and lesbian representation in film. It fills a gap in the scholarship on the film communities of this period, by interrogating the role gay and lesbian filmmaking groups played in creating a national gay and lesbian cinema culture, and raises questions about how the political and social are expressed through filmmaking within marginalised communities. By exploring the experience of two gay and lesbian filmmaking groups, it will show the ways in which questions of audience and representation influenced the political and aesthetic style of early Australian gay and lesbian film culture.